Managing fiscal risks: Lessons from case studies of selected OECD countries - Moretti, Delphine (OECD Publishing, 2021)
Based on five case studies, this paper looks at the definition and classification of fiscal risks; sets out the components of a comprehensive fiscal risks framework; and examines how to operationalise such a framework. It then summarises challenges and key lessons to be considered by countries that wish to implement OECD recommendations in this area to increase the resilience of their public finances in the wake of the COVID-19 outbreak